The Implementation of the Main Mandate and Wider Mandate Concepts in the Curriculum Design of (Future) State Christian University in Indonesia - Paul Lumbantobing (LPPM IAKN Tarutung, 2021)
The transformation of Christian State Religious Higher Education (SRHE) into State Christian University (SCU) should be able to answer various basic questions regarding their existence, governance and outcomes, thereby convincing various stakeholders that the existence of SCUs is indispensable in every era and will graduate alumni who have a significant impact on the progress of society, nation and state. The concept of the main mandate and wider mandate of the Indonesian Ministry of Religion can be elaborated, and operationalized by the leadership of Christian SRHE in responding to the challenges and expectations of stakeholders. The challenges and expectations for the existence of SCU can be met holistically through the management of vertical elements in the form of prayer, the Word of God, churches, sacraments, fellowship and ministry as well as the management of horizontal elements in the form of lecturer, curriculum, students, as well as soft and hard infrastructure of organization. This paper aims to answer these challenges through one element, namely the curriculum, by outlining the concept of curriculum design that synergizes Christian values and knowledge (as the main mandate) and other sciences (wider mandate). This article was developed through literature study and analysis and how to synergize various elements of higher education in a concept that underlies curriculum design that gives Christian SRHE and its graduates uniqueness. Based on the study and analysis of the literature, it is found that the main mandate and wider mandate concepts can be correlated with theological concepts in the form of special revelation, general revelation as well as gospel mandates and cultural mandates. In curriculum design, the main mandate can be represented by the development of the Christian Liberal Arts, and the wider mandate can be represented by the functional science due to study programs that will be opened at SCU.